A literature review of common factors affecting labor productivity in Asia: 25 years of insight - Søren M. Lindhard; Sanaz Sadeghi; Nazi Soltanmohammadlou; Simon Wyke (Journal of Civil Engineering and Management)
Construction is one of the largest sectors of the Asian economy as it accounts for approximately 14.8% of Asia’s GDP. This, together with the fact that labor productivity is a key factor affecting project performance, makes enhancement of productivity a significant contributor to economic growth. Yet, previous studies have not provided a well-defined terminology together with an understanding of the prioritization of factors, which decision-makers need to take into consideration to enhance productivity in a structured manner. A structured literature review has been carried out, focusing on identifying factors affecting labor productivity in Asia, and calculating the aggregated rank. Hypothesis-testing revealed that the ranking could be generalized across the different regions in Asia. A full rank aggregation considering Asia as a whole reveals the five most important factors to be: “Incomplete design”, “Skill and experience (of laborers)”, “Competency of the project manager”, Materials”, and “Client and consultants”. Today’s research on factors affecting labor productivity is fragmented. By making a structured rank aggregation, and comparing findings between studies, a unifying understanding to the relative importance of factors affecting labor productivity has been established. The relative importance gives input to on-site mangers and helps enhancing managerial strategies to improve labor productivity.